Associations of adherence to Mediterranean-like diet pattern with incident rosacea: A prospective cohort study of government employees in China - Chen, Peng; Yang, Ziye; Fan, Zhihua; Wang, Ben; Tang, Yan; Xiao, Yi; Chen, Xiang; Luo, Dan; Xiao, Shuiyuan; Li, Ji; Xie, Hongfu; Shen, Minxue (Frontiers in Nutrition, 2023)
ABSTRACT Background: Despite of growing evidence on gastrointestinal comorbidities of rosacea, there was a lack of literatures regarding the role of diet on rosacea. Objectives: To investigate the relationship between adherence to a Mediterranean-like diet pattern and the risk of incident rosacea. Methods: This was a prospective cohort study of government employees aged >20 years conducted between January 2018 and December 2021 from 5 cities of Hunan province of China. At baseline, participants completed a food frequency questionnaire and participated in a skin examination. Presence of rosacea was determined by certified dermatologists. Subsequent skin examinations during follow-up were performed every one-year interval since the entry of the study. The Mediterranean diet score (MDS) was generated based on 7 food groups (whole grains, red meats, fish, raw vegetables, legumes, fruits and nuts). Binary logistic regression models adjusted for potential confounders were used to estimate risks for incident rosacea. Results: Of the 3773 participants who completed at least two consecutive skin examinations, 3496 were eligible for primary analyses. With a total follow-up of 8668 person-years, we identified 83 incident rosacea cases. After full adjustments for covariates, the MDS was associated a decreased risk of incident rosacea (aOR: 0.84, 95%CI: 0.72, 0.99; Ptrend = 0.037 for 1-point increment of MDS). In subgroup analyses by body mass index (BMI), this inverse association was consistently observed in the lowest and medium tertiles of BMI (<24.5 kg/m2), but not in the highest tertile of BMI (≥24.5 kg/m2), with a significant interaction effect (P <0.001). Conclusions: Our results suggested that adherence to a Mediterranean-like diet pattern might reduce the risk of incident rosacea among non-overweight individuals.